A novel method to calculate pressure on the twin-tunnel in layered strata - Lyu, Hai-Min (MethodsX, 2020)
Tunnel pressure from the surrounding rocks plays a critical role for the safety of tunnel. The existing methods for calculate twin-tunnel pressure supposed that the tunnel is buried in a uniform soil layer. This work presents detailed equations of an analytical method to calculate the twin-tunnel pressure in layered strata, which can consider the effects from soil layers. The proposed method is applied to analyse the pressure of the metro twin-tunnels in Chongqing. To demonstrate the efficiency of the proposed analytical method, both the tunnel pressure in layered strata and single strata were calculated. The method article is a companion paper with the original article [1]. • Analyses of the soil parameters; • Determine the failure pattern A/B; • Calculate the vertical and horizontal pressure.